2020
DOI: 10.1016/j.cub.2019.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Motor Behavior Selectively Inhibits Hair Cells Activated by Forward Motion in the Lateral Line of Zebrafish

Abstract: Highlights d Efferents in neuromasts of the lateral line convey a close copy of the motor signal d Efferents suppress hair cell glutamate release within 50 ms of first motor spike d Efferent modulation is biased toward hair cells activated during forward motion d Motor activity blocks ''push-pull'' signaling of stimulus direction

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 52 publications
9
71
0
Order By: Relevance
“…Viewed this way, the emphasis on h-t flow processing that we observe is unsurprising, since this type of flow would be more common, and likely more ethologically relevant, to larval zebrafish. Recent observations of specific silencing of the h-t flow response at the neuromast level by efferent copies during self-motion also support an ethological relevance to the h-t flow (Pichler and Lagnado, 2020). However, the paralyzing agent we used blocks the cholinergic receptors that mediate this silencing by the motor neurons, and we did not observe swim bouts as a result of our stimuli.…”
Section: Coding Of Detailed Information About H-t Water Flowsupporting
confidence: 74%
“…Viewed this way, the emphasis on h-t flow processing that we observe is unsurprising, since this type of flow would be more common, and likely more ethologically relevant, to larval zebrafish. Recent observations of specific silencing of the h-t flow response at the neuromast level by efferent copies during self-motion also support an ethological relevance to the h-t flow (Pichler and Lagnado, 2020). However, the paralyzing agent we used blocks the cholinergic receptors that mediate this silencing by the motor neurons, and we did not observe swim bouts as a result of our stimuli.…”
Section: Coding Of Detailed Information About H-t Water Flowsupporting
confidence: 74%
“…However, only one efferent fiber contacts all HC of a single neuromast (Faucherre et al, 2009;Dow et al, 2018). Moreover, during fictive locomotion presynaptic activity across all efferent synapses within a neuromast are synchronously activated (Pichler and Lagnado, 2020). Similarly, in our experiments ACh-mediated effects were observed in HC irrespective of their polarity and the median magnitude of inhibition in both cases showed no significant difference.…”
Section: Discussionsupporting
confidence: 60%
“…Scyliorhynus, inhibits spontaneous and evoked activity of afferents by generating inhibitory postsynaptic potentials in HC Roberts and Russell, 1972;Flock and Russell, 1976). In zebrafish, activation of cholinergic efferents suppresses glutamate release from HC (Pichler and Lagnado, 2020) and inhibits afferent activity (Lunsford et al, 2019). This most likely results from ACh-evoked hyperpolarization of HC and reduced Ca 2+ influx through voltageactivated Ca 2+ channels.…”
Section: Stimulation Of Cholinergic Efferents In the Ll Of Xenopus Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been shown that the connections between afferent neurons and hair-cell bundles of the LL neuromast develop independently of experience in larval zebrafish [Nagiel et al, 2009], this sensory organ shows several filtering properties whose development might depend on experience. For instance, efferent copies of forward motion suppress synaptic transmission in lateral line hair cells [Pichler and Lagnado, 2020], and canal neuromasts are capable of sensing water vibrations even against a background of unidirectional water flow [Engelmann et al, 2002]. Such fine-tuning of LL sensing under specialized conditions could be shaped through the sensory experiences of the presence of conspecifics.…”
Section: Discussionmentioning
confidence: 99%